O planejamento tributário sob a perspectiva da análise econômica do direito - Drehmer, Frederico Luiz Streppel (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation aimed to evaluate tax planning through the lens of Economic Analysis of Law. The study started from the notion that the acts and businesses resulting from tax planning are subject of intense doctrinal and jurisprudential divergence, especially in the administrative scope, about the normative limits to the practices used by taxpayers in order to reduce, eliminate or postpone the incidence of taxes, which does not prevent its wide use. An introductory outline of taxation was presented in order to reach the exposition of the current state of the matter. Concepts and divergences were sought in the contemporary doctrinal and jurisprudential panorama, in order to expose the current institutional environment. In parallel, were presented the instruments extracted from schools typically linked to the Economic Analysis of Law used in the study. Ronald Coase's Transaction Cost Theory, Gary Becker's Economics of Crime, with special attention to the incursion carried out by Michael G. Allingham and Angmar Sandmo in the tax sphere, and the Agency Problem, by Armen Alchian and Harold Demsetz, had its essential core of understanding invoked for analysis. On the other hand, legal certainty was taken as a qualitative reference of the legal system, seeking in Humberto Ávila the basic understanding of the subject, as well as economic efficiency. Based on this, the incentive structure related to the people involved in tax planning and the transaction costs characteristically associated with the practices were presented. This understanding made it possible to present the final propositions with the recommendations that are considered adequate to correct the perverse incentives identified in the current institutional environment of tax planning.
Keywords: Tributos; Planejamento tributário; Evasão; Segurança jurídica; Estrutura de incentivos; Taxes; Tax planning; Evasion; Legal certainty; Incentive structure; ACCNPQ::Ciências Sociais Aplicadas::Direito